Really fr ikr geez la we zz
Answer:
(f - g)(x) = -x² + 3x + 5
General Formulas and Concepts:
<u>Pre-Algebra</u>
<u>Algebra I</u>
- Function Notation
- Combining Like Terms
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 3x + 5
g(x) = x²
(f - g)(x) is f(x) - g(x)
<u>Step 2: Find (f - g)(x)</u>
- Substitute: (f - g)(x) = 3x + 5 - x²
- Rewrite: (f - g)(x) = -x² + 3x + 5
Answer:

Step-by-step explanation:

The interval notation is (-12, 12).

3 points. Do the vertical line test.
Answer:
The answer is 2(the square root of 65 )
Step-by-step explanation:
Plug ( -6, 2) and (8, 10) into the distance formula and solve.
Distance = the square root of ((x2 - x1)^2 + (y2 - y1)^2))
Distance = the square root of ((8 - -6)^2 + (10 - 2)^2))
Distance = the square root of (14^2 + 8^2)
Distance = the square root of (196 + 64)
Distance = the square root of 260 which can be simplified to 2(the square root of 64)